Some Characteristics of Employees as Risk Factors for Presenteeism - Petra Mlakar; Janez Stare (Central European Public Administration Review)
Presenteeism, or the act of attending work while sick or despite feeling unwell, is a relatively new concept in the sphere of work. It is a phenomenon that has begun to be monitored more intensively around the world in the last decade. Presenteeism can affect an employee’s work in various ways and its consequences mean that it is already a problem in itself. Employers devote too little attention to it or are frequently not even aware of it. The majority of employers are in fact too often focused on the growing problem of absence from work because of sickness (absenteeism) and on eliminating the negative consequences of absenteeism, and do not (yet) see presenteeism as a problem. The research presented in this article deals with the question of the impact of employee characteristics on the phenomenon of presenteeism. The characteristics considered included ambition, financial worries, job security, sick leave and the physical and mental health of employees.